White Collar Overcriminalization: Deterrence, Plea Bargaining, and the Loss of Innocence - Dervan, Lucian E. (2013)
Overcriminalization takes many forms and impacts the American criminal justice system in varying ways. This article focuses on a select portion of this phenomenon by examining two types of overcriminalization prevalent in white collar criminal law. The first type of over criminalization discussed in this article is Congress’s propensity for increasing the maximum criminal penalties for white collar offenses in an effort to punish financial criminals more harshly while simultaneously deterring others. The second type of overcriminalization addressed is Congress’s tendency to create vague and overlapping criminal provisions in areas already criminalized in an effort to expand the tools available to prosecutors, increase the number of financial criminals prosecuted each year, and deter potential offenders. While these new provisions are not the most egregious examples of the overcriminalization phenomenon, they are important to consider due to their impact on significant statutes. In fact, they typically represent some of the most commonly charged offenses in the federal system. Through examination of the Sarbanes-Oxley Act of 2002 and examples of these two types of over criminalization within that law, this article seeks to understand whether new crimes and punishments really achieve their intended goals and, if not, what this tells us about and means for the over criminalization debate and the criminal justice system as a whole